2015
DOI: 10.1158/1535-7163.mct-14-0620
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphic CAG Repeat and Protein Expression of Androgen Receptor Gene in Colorectal Cancer

Abstract: Although somatic alterations in CAG repeats in the androgen receptor (AR) gene have been suggested to predispose to colorectal cancer, less is known about AR in colorectal cancer carcinogenesis. Because of lack of relevant analysis on CAG repeat length and AR expression in colorectal cancer, we aimed to investigate the prognostic value of polymorphic CAG and protein expression of the AR gene in patients with colorectal cancer. A case-control study was carried out on 550 patients with colorectal cancer and 540 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 24 publications
0
21
1
Order By: Relevance
“…24 Moreover, a case-control study showed that the CRC cases group had a longer cytosine-adenine-guanine (CAG) repeat length in the androgen receptor gene in comparison to controls in both males and females. 25 While another study has reported no association between the lengths of CAG repeats in the androgen receptor and CRC. 26 Testosterone may promote development of CRC via several possible pathways; however, further studies focusing on female populations are required to explain the possible role of testosterone in CRC tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…24 Moreover, a case-control study showed that the CRC cases group had a longer cytosine-adenine-guanine (CAG) repeat length in the androgen receptor gene in comparison to controls in both males and females. 25 While another study has reported no association between the lengths of CAG repeats in the androgen receptor and CRC. 26 Testosterone may promote development of CRC via several possible pathways; however, further studies focusing on female populations are required to explain the possible role of testosterone in CRC tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Male rats who underwent orchidectomy and administered with testosterone were more susceptible to tumor load compared to placebos . Moreover, a case–control study showed that the CRC cases group had a longer cytosine–adenine–guanine (CAG) repeat length in the androgen receptor gene in comparison to controls in both males and females . While another study has reported no association between the lengths of CAG repeats in the androgen receptor and CRC .…”
Section: Discussionmentioning
confidence: 99%
“…Breast cancer tissue microarrays (TMA) were used as described previously [23, 24] and immunohistochemically stained for AR, ER, PR, Her2, Ki67 and β-catenin expression levels. Briefly, after deparaffinization, sections were hydrated and underwent Ethylene Diamine Tetraacetic Acid (EDTA) buffer (pH 8.0) or sodium citrate buffer (pH 6.0) retrieval.…”
Section: Methodsmentioning
confidence: 99%
“…These CAG can alter the function of the AR gene. A case-control study investigating the effect of this polymorphism on CRC risk was carried out on 550 CRC cases and 540 healthy controls, who were analysed for presence of CAG sequences in the AR gene using polymerase chain reaction (PCR) [43]. The study showed that the CRC group had a longer CAG repeat length compared to the control group and that this repeat confers an increased risk of developing CRC in both males and females, whereas a shorter CAG repeat size may protect individuals against CRC.…”
Section: Role Of Testosterone In Colorectal Carcinomamentioning
confidence: 99%
“…In addition, the absence of AR expression in long CAG repeat sequences was associated with tumour size larger than 5 cm in diameter, which were moderate to poorly differentiated (at T3–T4 and N1–2 stages) compared to those with normal expression of AR and short CAG repeat sequences. Aside from the link to tumour stage, these patients were also reported to have a poor survival rate even after postoperative adjuvant chemotherapy as they demonstrated greater risk of recurrence or metastasis [43]. On the contrary, a different study has reported that there is no association between the length of CAG repeats in the AR and colorectal cancer.…”
Section: Role Of Testosterone In Colorectal Carcinomamentioning
confidence: 99%